A Study of the Effects of an Individual's Personality and Characteristics on Job Behavior Using the Myers-Briggs Type Indicator (International Journal of Innovative Research in Engineering & Management, 2023)
The Myers-Briggs Type Indicator (MBTI)  personality test is becoming increasingly commonly used  and acknowledged in many fields as a way to identify  personality, and some businesses are starting to implement  it in many workplaces to assist businesses increase  productivity. This study tries to describe the ways in which  MBTI can be used to determine an individual's traits in  work behaviours, especially when dealing with other  people, tasks, assessments, and friendship prospects.  To come to a conclusion about how a person's personality  and features affect their behaviour at work, this research  uses an integrated method of literature review. For the  purpose of understanding and interpreting this integrative  literature study, numerous guidelines and case-based  examples have been explored. It still has certain drawbacks,  and there are just a few prior research. Future research in  this area will be required to adapt.
Keywords: Job Behaviour; Myers-Briggs Type Indicator; Performance; Personality Traits; Personality Assessment